Co‐crystal structure of the Fusobacterium ulcerans ZTP riboswitch using an X‐ray free‐electron laser. Issue 7 (8th July 2019) - Jones, Christopher; Tran, Brandon; Conrad, Chelsie; Stagno, Jason; Trachman, Robert; Fischer, Pontus; Meents, Alke; Ferré-D'Amaré, Adrian
Abstract : An X‐ray free‐electron laser was used to determine the structure of the ZTP riboswitch, an RNA motif that is responsible for regulating gene expression in bacteria. Abstract : Riboswitches are conformationally dynamic RNAs that regulate gene expression by binding specific small molecules. ZTP riboswitches bind the purine‐biosynthetic intermediate 5‐aminoimidazole‐4‐carboxamide riboside 5′‐monophosphate (ZMP) and its triphosphorylated form (ZTP). Ligand binding to this riboswitch ultimately upregulates genes involved in folate and purine metabolism. Using an X‐ray free‐electron laser (XFEL), the room‐temperature structure of the Fusobacterium ulcerans ZTP riboswitch bound to ZMP has now been determined at 4.1 Å resolution. This model, which was refined against a data set from ∼750 diffraction images (each from a single crystal), was found to be consistent with that previously obtained from data collected at 100 K using conventional synchrotron X‐radiation. These experiments demonstrate the feasibility of time‐resolved XFEL experiments to understand how the ZTP riboswitch accommodates cognate ligand binding.